Toxicity of neem and pyrethrum extracts to adult grass grub - Qureshi, M.S.; Jackson, T.A.; Townsend, R.J.; Saville, D.J. (New Zealand Plant Protection, 2002)
Grass grub Costelytra zealandica larvae damage pastures and crops by root feeding while the adult beetles can be serious defoliators of a wide range of plants Control of this pest with botanical insecticides has received little attention The objectives of this study were to investigate the direct effects of neem and pyrethrum extracts on the adult beetle A laboratory bioassay was used to test the acute and chronic effects of the botanicals over a range of doses by treating a food source (Pittosporum tenuifolium) with the extracts Pyrethrum had the faster action; at all doses beetles were killed within a day Neem caused only low mortality even at the highest rate Similar results were obtained when the bioassays were repeated using the same treatments for Smiths chafer (Odontria smithii) beetle Further research is needed on the practical implications of these results